AB0362 Non-compliance to classical dmards associated in biological therapy regimes: the characteristics of patients. (23rd January 2014) - Gudu, T. E.; Berghea, F.; Peltea, A.; Iacob, D.; Predeteanu, D.; Balanescu, A.; Bojinca, V.; Constantinescu, C.; Abobului, M.; Vlad, V.; Opris, D.; Isac, L.; et al.
Abstract : Background: Non-biological DMARDs are important treatment in rheumatic patients that receive biological therapy. In the absence of the first ones the final outcome may be jeopardized despite a full adherence to the rest of regimes. In real practice a patient receive a biological therapy in addition to an existing non-biological DMARD regime, a regime that was not sufficient to control the disease. However the patient is not always informed enough to understand the important role of a treatment that was not so good in the past – non-biological DMARDs. That explains why some patients reduce their classical DMARDS usage; is important to know better their profile in order to focus the efforts in their education. Objectives: To characterize the profile of the rheumatic patient with impaired adherence to non-biological DMARDs during mixed (biological and nonbiological) treatment regimes. Methods: In a focus group exercise we defined several characteristics (of the rheumatic patient) that could impact the adherence to non-biological DMARDs. We selected education, income, total number of distinct drugs used daily, perceived effect of previous regime, perceived effect of new regime to be analyzed in addition to regular patient's characteristics (sex, age and living area). A structured questionnaire have been developed and delivered to 50 rheumatic patients consecutive admitted. Statistic analyses have been done with SPSS 16.0 Results: We split the lot of responders in highly adherent (HA) group – no or just a few doses of nonbiologic DMARD not used and poor adherent (PA) group – many to all doses of drug not used. The sex ratio was different in HA group (female: male ratio was 6:1 in HA and 10:1 in PA, p<0.05); age was different – mean (sd): 54.16 (15.6) in HA vs. 63.12 (10.2) in PA, p<0.05 and the proportion of patients that lived in rural area was higher in PA group (38.5% vs 29.7%, p<0.05). HA group included more educated persons than PA (with more persons having at least 12 years of formal education in HA group – 81.3% vs, 61.2% p<0.05). No difference between groups regarding the annual income was found – this is explicable, both biologic and non-biologic DMARDs are highly reimbursed in the two groups. Only 27% in HA group considered that the total number of drugs they need to use daily is too high vs. 54% (p<0.01) in PA group. 54% from HA were still on cortisone vs. 35% (p<0.05) in PA but Patient Global Assessment regarding the health status was similar in both groups (71.8 points in HA versus 69.8 in PA group, p>0.05). Other sub-group analyses have been done, too including patient's opinion regarding the potency of biological ad non-biological DMARDs. Conclusions: The patient adherent to non-biological part of their mixed treatment regime has a different profile that the one who is non adherent. In addition there is a difference between those who are non-adherent to any kind of medication and those who ignore just the non-biological part of their regime. The understanding of these differences might be helpful in evaluation of the results of clinical trials. Disclosure of Interest: None Declared